2014
DOI: 10.1590/0103-6440201302383
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bone Healing in Rabbit Calvaria Grafted with Three Different Biomaterials

Abstract: This study evaluated the bone regeneration process in rabbit calvaria induced by three types of biomaterials: two xenogenous, consisting of deproteinized bovine bone, while the other was alloplastic, based on biphasic calcium phosphate. Five New Zealand white rabbits weighing between 2,900 and 3,500 g were submitted to four standard 8 mm-diameter perforations at the parietal bone. Three perforations were filled with three grafts and biomaterials, two of them received bovine Bio-Oss® and Endobon® Xenograft Gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
5
16
1
Order By: Relevance
“…This evidence was observed in Figure 1a-c,g-i,m-o, as well as in Figure 2a-c. This was also confirmed by previous studies [41,42]. For example, Takauti [31] studied the bone regeneration process in rat calvariae, with defects filled with three different types of biomaterials: two xenografts (deproteinized bovine bone) and one allograft (biphasic calcium phosphate).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This evidence was observed in Figure 1a-c,g-i,m-o, as well as in Figure 2a-c. This was also confirmed by previous studies [41,42]. For example, Takauti [31] studied the bone regeneration process in rat calvariae, with defects filled with three different types of biomaterials: two xenografts (deproteinized bovine bone) and one allograft (biphasic calcium phosphate).…”
Section: Discussionsupporting
confidence: 80%
“…In this context, numerous studies have been also conducted in animal models on the osteogenic properties of different biomaterials, with different outcomes [41][42][43][44][45]. However, photobiomodulation effects, in combination with biomaterials in bone defect repair processes, require further study, as different responses from the host have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this has influenced lot of attention towards biomaterial science thereby influencing tissue engineering offering new and promising alternatives for existing traditional implants [1], prostheses in orthopedics [2], dentistry [3] and organ and tissue replacement [4]. Further, among various existing biomaterials such as bovine bone, recent trend shows that calcium phosphate is often used as bone substitute mainly due to its chemical similarities with that of mineral component of bones and hard tissues, therefore, proved to improve bone healing in rabbit calvaria [5]. In this regard, lots of approaches are considered for extraction of calcium phosphate from bovine bones [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, to be effective, SB requires enhanced rate of bone formation, because its β -tricalcium phosphate component is resorbed and the defect must be filled almost entirely by new bone ( Figure 4(a) ). This different behavior was already discussed in the literature in a different rabbit model of biphasic calcium phosphate versus BS bone regeneration experiment [ 48 ]. The different profile of cytokine expression detected in vitro underlines the onset of different and specific healing mechanisms, fit for the specific nature of both materials, hence the satisfactory results reported in the literature [ 16 , 18 26 ].…”
Section: Discussionmentioning
confidence: 65%